War Hypotheses: Drug Trafficking, Sovereignty and the Armed Forces in Mexico. - FONDEVILA, GUSTAVO; QUINTANA‐NAVARRETE, MIGUEL (Bulletin of Latin American Research, 2015)
This essay analyses how Mexican presidents have interpreted the concepts of drug trafficking and national security and how these particular connotations have redefined national sovereignty and the specific role of the armed forces in protecting this sovereignty. A qualitative technique of discourse analysis is used to examine public speeches by Zedillo (1994-2000), Fox (2000-2006) and Calderón (2006-2012). The conclusions suggest that drug trafficking and US omnipresence are the two main issues that shaped Mexico's national security threats during this period, with qualitatively distinct trajectories.